Spatial Variability in Photosynthetic Characteristics of Ice Algae in Saroma-ko Lagoon, Hokkaido - Kayoko, Takimoto; Mitsuko, Obata; Ai, Murata; Shozo, Motokawa; Satoru, Taguchi (2010)
第32回極域生物シンポジウム ポスター発表 conference object